2012
DOI: 10.1002/pros.22497
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of prostate cancer‐associated stromal cells to embryonic stem‐like

Abstract: Genes of CP stromal cells could be fully inactivated by genetic reprogramming. As a consequence, the disease phenotype was 'cured'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 37 publications
(68 reference statements)
1
35
0
Order By: Relevance
“…Cells without CD59 might, therefore, be resistant to the effect of AGR2. Another possible future study could determine the effect of secreted AGR2 on stem cells such as the induced pluripotent stem cells generated from reprogramming of prostate stromal cells [35], given its function in organ regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Cells without CD59 might, therefore, be resistant to the effect of AGR2. Another possible future study could determine the effect of secreted AGR2 on stem cells such as the induced pluripotent stem cells generated from reprogramming of prostate stromal cells [35], given its function in organ regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…8,23e26 Lin28 controls the biogenesis of let-7 miRNAs 27,28 and is one of the pluripotency factors that are responsible for the reprogramming of differentiated cells to stem cell like. 29 In this study, we showed that Lin28 is overexpressed in human CaP compared to benign tissues, promotes growth of human CaP cells in vitro, and enhances growth of CaP xenografts. To our knowledge, this is the first report demonstrating the role of Lin28 in CaP cell proliferation and the ability of Lin28 to promote prostate tumor growth.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, it was reported that MAGEA2 binds with the p53 tumour suppressor protein to repress p53 transcriptional activity by recruiting the histone deacetylase HDAC3 . In stem cell biology, it is well known that undifferentiated human embryonic stem cells express various MAGEA family proteins, including MAGEA2 . When human embryonic stem cells were differentiated into EBs and teratomas, the expression levels of MAGEA family members were spontaneously regulated .…”
Section: Introductionmentioning
confidence: 99%
“…18,23 In stem cell biology, it is well known that undifferentiated human embryonic stem cells express various MAGEA family proteins, including MAGEA2. 24,25 When human embryonic stem cells were differentiated into EBs and teratomas, the expression levels of MAGEA family members were spontaneously regulated. 26 Therefore, many biologists have predicted that MAGEA proteins are highly expressed and play a critical role in iPS cells, but their specific functions have remained unknown.…”
mentioning
confidence: 99%